Rent as management of housing insecurity: possibilities of the securitization of the right to housing - de Andrade Guerreiro, Isadora (2020)
The paper seeks to understand new real estate rental dynamics in informal territories in São Paulo in light of the macro-structural transformations that consolidated the predominance of reproduction of fictitious capital – which shifted wage relations, mechanisms of income extraction, and draw new outlines for the role of the state. The hypothesis is that, with the increment in “shapeless” wage relations at the margins of capitalism, the role of popular rent gains in relevance as it forms of a new way of life marked by permanent housing insecurity. This dynamic is motivated and regulated by right to housing public policies that are producing and connecting this insecurity to the possibility of financial gains, resulting in a favorable environment for private land management regimes.